2022
DOI: 10.1101/2022.02.25.481978
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transcriptomic analysis of sorted lung cells revealed a proviral activity of the NF-κB pathway towards SARS-CoV-2

Abstract: Detailed knowledge of cellular networks that are modulated by Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is needed to understand viral replication and host response. So far, transcriptomic analyses of interactions between SARS-CoV-2 and cells were performed on mixed populations of infected and uninfected cells or using single-cell RNA sequencing, both leading to inaccurate or low-resolution gene expression interpretations. Moreover, they generally focused on annotated messenger RNAs (mRNAs), … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 105 publications
(192 reference statements)
0
3
0
Order By: Relevance
“…SARS-CoV-2 Nsp14 induces the NF-κB signaling and downstream cytokines, which may support the host cell proliferation and survival, or prevent cell apoptosis, thus benefiting viral replication ( 42 , 76 ). As the supportive evidence, a recent study showed that knockdown of NF-κB p50 or IL-8 indeed impairs SARS-CoV-2 viral RNA expression and its replication in A549-ACE2 cells ( 64 ). RIB and MPA are both FDA-approved drugs for treating HCV infection and transplant organ rejection, respectively.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…SARS-CoV-2 Nsp14 induces the NF-κB signaling and downstream cytokines, which may support the host cell proliferation and survival, or prevent cell apoptosis, thus benefiting viral replication ( 42 , 76 ). As the supportive evidence, a recent study showed that knockdown of NF-κB p50 or IL-8 indeed impairs SARS-CoV-2 viral RNA expression and its replication in A549-ACE2 cells ( 64 ). RIB and MPA are both FDA-approved drugs for treating HCV infection and transplant organ rejection, respectively.…”
Section: Discussionmentioning
confidence: 82%
“…IL-8 may attract neutrophils, stimulate granulocytes’ response to tissue damage, and generate ARDS-related micro thrombosis ( 62 , 63 ). IL-8 induction could initiate a positive feedback via autocrine of attracted neutrophils ( 63 ), which may also support viral replication of SARS-CoV-2 ( 64 ) and inhibit SARS-CoV-2 specific T-cell responses ( 65 ). In terms of possible molecular mechanisms, since IMPDH2 participates in regulating the host nucleotide metabolism ( 66 , 67 ), it may further modulate cellular stress response and downstream NF-κB activation ( 67 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, SARS-CoV-2 is known to benefit from the upregulation of the inflammatory response, mainly through the NF-kB pathway, which is essential for the replication and propagation of the virus (Nilsson-Payant et al, 2021). A very recent study confirmed the proviral role of the NF-kB pathway in SARS-CoV-2 infected lung cells (Bhargava et al, 2023).…”
Section: Discussionmentioning
confidence: 77%